Pembelajaran Pendidikan Agama Islam Berbasis Interdisipliner Psikologi dan Sosiologi di SMPN 6 Sukabumi - didin Didin; Mulyawan Safwandy Nugraha (CV. Berkah Cakrawala Inspirasi, 2025)
This study examines the implementation of an interdisciplinary approach integrating educational psychology and sociology in Islamic Religious Education (IRE) learning at SMPN 6 Sukabumi. The research focuses on how psychological support and sociological practices are applied in classroom learning amid structural constraints, particularly those related to teacher workload and limited educational resources. Using a qualitative field study design, data were collected through classroom observations, in-depth interviews with one IRE teacher and selected students, and analysis of instructional documents. The findings reveal that the integration of psychological approaches, such as emotional support, personal teacher-student relationships, and motivational strategies, enhances students’ engagement and facilitates meaningful internalization of Islamic values. Simultaneously, sociological integration is reflected in collective religious practices and school culture, which reinforce values through sustained social interaction. The study highlights that the effectiveness of this interdisciplinary learning model is strongly supported by teachers’ pedagogical resilience, enabling innovation despite structural limitations. However, the sustainability of such practices remains challenged by excessive teacher workload, limited facilities, and policy fragmentation. The study contributes theoretically by demonstrating the practical applicability of interdisciplinary approaches in IRE and practically by emphasizing the need for systemic support to ensure the continuity of innovative and contextual religious education.